REVIEW ARTIKEL: KARAKTERISASI EDIBLE FILM DARI KARAGENAN RUMPUT LAUT (Eucheuma Cottoni/Kappaphycus alvarezii) - Nur, Nana Septiana; Pasaribu, Subur P.; Panggabean, Aman Sentosa (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Seaweed is a type of multicellular organism with fast growth. Seaweed is quite abundant and is in great demand in several fields, both industrial and pharmaceutical. There are 3 types of seaweed, including brown with polysaccharides such as alginate, fucoidan and laminarin. Green seaweed with polysaccharides such as ulvan. Red with polysaccharides such as agar and carrageenan. Carrageenan is a hydrocolloid of Kappaphycus alvarezii/Eucheuma cottonii which has been extracted with an alkaline solution or water. Carrageenan has the property of being able to form a stable gel, is edible, renewable and rich in fiber so it has the potential to be used as an edible film. Edible film is a layer that can be eaten and has a role as a barrier to moisture. Based on the literature, making edible film from seaweed carrageenan with a higher concentration of seaweed results in a decrease in the transmittance value and transparency level of the edible film. The addition of a higher concentration also produces edible film with a lower water content, namely 21.16%, and has a tendency for slower dissolution compared to lower seaweed concentrations. The higher the concentration of carrageenan used in making edible film, the higher its solubility, the stronger its tensile strength, the thicker and more resistant it is, and the lower the vapor transmission rate or the higher the ability to hold water. Keywords: Seaweed (Eucheuma cottonii), carrageenan, edible film